Association between dietary inflammatory and antioxidant potential and systemic inflammatory and oxidative status with the risk and severity of coronary artery disease - Zahra Namkhah; Elham Alipoor; Mahnaz Salmani; Negar Ebrahimi; Monireh Ahmadpanahi; Ali Vasheghani-Farahani; Mehdi Yaseri; Michael D. Wirth; Longgang Zhao; James R. Hebert; Mohammad Javad Hosseinzadeh-Attar (PLoS ONE, 2025)
Background and aims Unhealthy diets have pro-inflammatory properties that have been shown to contribute to coronary artery disease (CAD). The dietary inflammatory index (DII®) and the dietary antioxidant quality score (DAQS) quantify the anti-/pro-inflammatory and antioxidant potential of a diet. This study aims to investigate the association between the energy-adjusted DII (E-DIITM), DAQS, oxidant/anti-oxidant biomarkers, and CAD risk and severity. Methods and results This cross-sectional study investigated 158 participants for the presence and severity of CAD based on coronary angiography. E-DII and DAQS scores, malondialdehyde (MDA), total oxidant status (TOS), glutathione peroxidase (GPX) activity, total antioxidant capacity (TAC) and conventional cardiometabolic risk factors were assessed. The triglyceride-glucose (TyG) index and mean arterial pressure (MAP) were also calculated. No association was observed between the E-DII or DAQS and the presence or severity of CAD. Based on the final regression models, age (adjusted odds ratio (AOR) =1.07, P = 0.002), male sex (AOR = 5.02, P < 0.001), MAP (AOR = 1.03, P = 0.03), HDL-C (AOR = 1.04, P = 0.06) and hs-CRP (AOR = 1.06, P = 0.045) as well as TOS (AOR = 1.16, P = 0.03) and TAC (AOR = 1.51, P = 0.07) increased and GPX activity (AOR = 0.51, P = 0.07) decreased the odds of having CAD. Male sex (adjusted β (Aβ) =22.04, P < 0.001), age (Aβ = 0.87, P = 0.003), hs-CRP (Aβ = 0.72, P = 0.045) and TOS (Aβ = 2.75, P = 0.003) were associated with higher Gensini scores. Higher GPX activity (Aβ = −10.95, P = 0.03) was associated with lower Gensini scores. Conclusion Biomarkers of oxidative stress, including TOS, TAC, and GPX activity, were associated with the presence, extent or severity of coronary atherosclerosis while no associations were observed for E-DII and DAQS scores.